Anthropometric Measurements in Healthy Full-Term Iraqi Neonates: A Comprehensive Evaluation - Haider Adil Abdullah Al-Obaidi; Hawraa Sami Salkhi; Hussam Abdul Kareem Salal (Academic Journal of Clinicians, 2025)
Childhood growth has been the subject of much research given its importance in the field of pediatrics. Anthropometric measures are used worldwide to assess intrauterine nutritional status, fetal growth and the success of prenatal care, improving the chances of good health during pregnancy, the first year of life, and early childhood. In Iraq, there still a need to estimate standard measurements for health full-term Iraqi neonates. The objective of this study is estimating the normal anthropometric measurements in healthy Iraqi full-term neonates and comprehensive evaluation of the effect of maternal, antenatal and sociodemographic factors on these measurements. We utilized a cross-sectional design study and conducted this study during a period of 22 months (April-2023 to February 2025). We included a total of 642 full-term single tone neonates of both genders who were delivered in Karbala city during the study period. Anthropometric measurements included body weight, supine length and occipitofrontal circumference (OFC). Standard methods were applied in all measurements. Our findings revealed a reference range for the anthropometric measurements of full-term healthy neonates in our province. Anthropometric parameters can significantly be affected by maternal factors. However, the studied anthropometric parameters of Iraqi neonates in this study were lower than the standard NCHS levels.